2021
DOI: 10.1186/s12911-021-01625-4
|View full text |Cite
|
Sign up to set email alerts
|

Middle-aged and elderly users’ continuous usage intention of health maintenance-oriented WeChat official accounts: empirical study based on a hybrid model in China

Abstract: Background Although middle-aged and elderly users are the main group targeted by health maintenance-oriented WeChat official accounts (HM-WOAs), few studies have explored the relationship of these accounts and their users. Exploring the factors that influence the continuous adoption of WOAs is helpful to strengthen the health education of middle-aged and elderly individuals. Objective We developed a new theoretical model and explored the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Consistent with previous research ( 19 , 49 52 ), this study demonstrated that the public’s performance expectancy, social influence, hedonic motivation, and habit perception directly and positively influence women’s continued intention to use women’s health WeChat public accounts. This suggests that the UTAUT2 model exhibits consistency in explaining the influencing factors of user’s continued intention to use health WeChat public accounts targeting different audiences and content.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous research ( 19 , 49 52 ), this study demonstrated that the public’s performance expectancy, social influence, hedonic motivation, and habit perception directly and positively influence women’s continued intention to use women’s health WeChat public accounts. This suggests that the UTAUT2 model exhibits consistency in explaining the influencing factors of user’s continued intention to use health WeChat public accounts targeting different audiences and content.…”
Section: Discussionsupporting
confidence: 89%
“…(1) UTAUT2: Adapted from the original scale by Venkatesh et al ( 14 ) and previous studies ( 19 , 41 , 42 ), this section measured the public’s intention to sustain the use of women’s health WeChat official accounts. It consisted of 7 dimensions with 25 items: behavioral intention (3 items), performance expectancy (3 items), effort expectancy (4 items), social influence (4 items), facilitating conditions (3 items), hedonic motivation (3 items), and habit (4 items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because daily internet use has become a normal part of life for middle-aged and elderly individuals. They use the internet for various purposes, such as seeking health information [ 73 ], chatting, watching the news, and making mobile payments [ 74 ]. All of these activities help them integrate into digital life without experiencing the negative effects of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The constructs from the HBM have been applied to predict health-related Internet usage. 74 , 75 Among them, the perceived benefit is an important antecedent when deriving the usage intention regarding chatbots. 27 Moreover, self-efficacy, which is one's confidence in gaining positive outcomes through computer-mediated actions, has been confirmed to positively affect the usage intention in previous research.…”
Section: Literature Reviewmentioning
confidence: 99%